2019
DOI: 10.1186/s40691-019-0182-4
|View full text |Cite
|
Sign up to set email alerts
|

Convert one outfit to more looks: factors influencing young female college consumers’ intention to purchase transformable apparel

Abstract: Transformable apparel offers two or more functional and/or alternative aesthetic styles through various manipulative methods, which is considered a sustainable alternative in the fashion industry to reduce excess clothing consumption. The study intends to identify the influences of environmental apparel knowledge, environmental beliefs, and personal values on consumers' intention to purchase transformable apparel products. The theory of reasoned action (TRA) was applied as the foundation for the conceptual fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The study found that the EC and EB of sustainable masks positively affected PI through consumers’ EA and SN. However, EC had no effect on SN, suggesting that consumers’ EC and EB play an important role in the PI of sustainable masks; this is consistent with the findings of previous pro-environmental consumption studies (Lang & Wei, 2019 ; Pagiaslis & Krontalis, 2014 ). The fact that the EC does not affect SN reveals that concerns about the environment should increase the PI of sustainable masks, regardless of people’s opinions and beliefs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The study found that the EC and EB of sustainable masks positively affected PI through consumers’ EA and SN. However, EC had no effect on SN, suggesting that consumers’ EC and EB play an important role in the PI of sustainable masks; this is consistent with the findings of previous pro-environmental consumption studies (Lang & Wei, 2019 ; Pagiaslis & Krontalis, 2014 ). The fact that the EC does not affect SN reveals that concerns about the environment should increase the PI of sustainable masks, regardless of people’s opinions and beliefs.…”
Section: Discussionsupporting
confidence: 90%
“…Research finds significant correlation between EB and consumer behavior. In studies of apparel (Lang & Wei, 2019 ), and biofuels (Pagiaslis & Krontalis, 2014 ), EB was found to have a positive effect on sustainable consumption behavior. Therefore, consumers using sustainable masks are likely to be aware of environmental pollution; that is, consumers with a high interest in the environment will have strong EBs.…”
Section: Conceptual Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Textile products purchase of a consumer is influenced by the consumers' attitude, product properties, care instructions and size. Apparel products purchase is positively influenced by the individuals attitude, environmental apparel knowledge and belief [14].Hence, the label is playing an important role in providing product properties and specification and thus resulting consumers' attitude and purchase decision [15,16]. The research on textile label is focusing on various aspects such as specification, consumer comprehension, social impacts, environmental impacts, economic impacts and health care [17].…”
Section: B Knowledge On Textile and Clothing Caring Characteristicsmentioning
confidence: 99%
“…The algorithm of manipulative actions in transformed clothing is based on the concept of argumentation of aesthetic values in the preservation of functional properties [9]. Accordingly, the research aimed at enhancing the comfort of a corset by means of regulating modeling effects on body sections should be considered relevant.…”
Section: Introductionmentioning
confidence: 99%